Metabolic, Enzymatic Activity, and Transcriptomic Analysis Reveals the Mechanism Underlying the Lack of Characteristic Floral Scent in Apricot Mei Varieties - Bao, Fei; Zhang, Tengxun; Ding, Anqi; Ding, Aiqin; Yang, Weiru; Wang, Jia; Cheng, Tangren; Zhang, Qixiang (Frontiers in Plant Science, 2020)
Apricot mei, a hybrid of Prunus mume and Prunus sibirica, usually has greater cold resistance than P. mume; however, most varieties of Apricot mei lack the characteristic floral scent of P. mume. The volatile and intracellular metabolites, activity levels of key enzymes, and transcriptomes of blooming flowers were comprehensively investigated in five varieties of P. mume. Benzyl acetate and eugenol were determined to be the main components of the P. mume floral scent. However, benzyl benzoate and benzyl alcohol benzoyltransferase activity was detected in only the low-fragrance varieties ‘Dan Fenghou’ and ‘Yanxing’. No benzyl alcohol or benzaldehyde reductase (BAR) activity was detected in the non-fragrant variety ‘Fenghou’. PmBAR1 and PmBAR3 were identified as the key genes responsible for BAR activity. The lack of benzyl alcohol synthesis in the ‘Fenghou’ variety was caused by low activity of PmBAR1-Fen and low expression of PmBAR3. The 60 aa segment at the N-terminus of PmBAR3 was found to play an important role in its enzymatic activity. Correlation tests between floral scent metabolites and the transcriptomes of the five different scented varieties showed that some transcripts associated with hormones, stresses, posttranslational modifications and transporters may also play important regulatory roles in floral scent metabolism in the different varieties.